2020
DOI: 10.1002/ece3.7099
|View full text |Cite
|
Sign up to set email alerts
|

Divergent lineages in a semi‐arid mallee species, Eucalyptus behriana, correspond to a major geographic break in southeastern Australia

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…However, we must make sure to distinguish between an environmental condition maintaining a disjunction and a possible vicariance event. Long distance colonisation is unlikely in eucalypts given their lack of seed dispersal mechanisms [ 67 ] and has been assumed to not be a major factor in other eucalypt species with disjunct distributions [ 25 , 68 , 69 ]. This leads to the hypothesis that the populations in the eastern and western East Gippsland Lowlands must have had a more or less continuous area of occurrence at some point in the past and vicariance is responsible for the current disjunction between them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we must make sure to distinguish between an environmental condition maintaining a disjunction and a possible vicariance event. Long distance colonisation is unlikely in eucalypts given their lack of seed dispersal mechanisms [ 67 ] and has been assumed to not be a major factor in other eucalypt species with disjunct distributions [ 25 , 68 , 69 ]. This leads to the hypothesis that the populations in the eastern and western East Gippsland Lowlands must have had a more or less continuous area of occurrence at some point in the past and vicariance is responsible for the current disjunction between them.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that isolation of the Werribee River Catchment populations is relatively recent given their close genetic relationship to those on the Deddick River. Previous findings of Fahey et al [ 25 ] showed that the isolation of a population of another eucalypt species, E . behriana , at Long Forest in the Werribee River Catchment was one of the most recent vicariance events across the distribution of that species which otherwise occurs inland of the Great Dividing Range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Michael J. Bayly (ORCID: 0000-0001-6836-5493), Rachael Fowler (ORCID: 0000-0002-8953-7036), School of Biosciences, University of Melbourne, Australia: Mike Bayly, Rachael Fowler and their research group use DNA data to study the evolution, diversity and classification of the Australian flora including large and iconic plant groups such as eucalypts (Schuster et al, 2018), ferns (Ohlsen et al, 2020) and bryophytes (Meagher and Bayly, 2014). Their team uses high-throughput DNA sequencing for assembly of whole chloroplast genomes (Fahey et al, 2020, nuclear ribosomal arrays (Fowler et al, 2020) and genome-wide nuclear markers (Fahey et al, 2020). To expand their research on the Australian flora, a long-term collaboration was established with Bevan Buirchell for collection of native species from a range of genera including Eremophila.…”
Section: Natural Sciencementioning
confidence: 99%
“…Informed by the results of Yang et al (2016) in silico tests of digestion of the E. grandis W.Hill genome, the restriction enzymes EcoR1-HF and Msp1 were chosen for genome digestion to create the ddRADseq library. The library preparation and pooling followed the protocol of Fahey et al (2021). The resulting pool was quantified on a 2200 Tape Station (Agilent) using a D1000 kit and sequencing was undertaken at the Walter and Eliza Hall Institute of Medical Research (WEHI) Genomics Hub, Melbourne, Vic., Australia, on an Illumina NextSeq.…”
Section: Dna Isolation Library Preparation and Sequencingmentioning
confidence: 99%